The Use of Video “Sidoarjo Story Sound” to Improve Listening Ability and Recognize the Socio-Cultural Environment of Kindergarten Student - Candra Kartikasari; Hendratno; Andi Mariono (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2021)
The purpose of research to describe the ability to listen and recognize the socio-cultural environment through the use of video “Sidoarjo Story Sound” in kindergarten children group B. With the research subjects of children aged 5-6 years of group B at Happy Kids School Kindegarten in Sidoarjo with a total of 20 children. The research method uses experimental research with one group pretest-posttest design. Data collection instruments use descriptive quantitative statistical analysis techniques. The findings of this study showed that video “Sidoarjo Story Sound” can improve the ability to listen and recognize the socio-cultural environment in group B by 0.88 with a high category and 0.97 with a high category. Implication of the research can combine Sidoarjo Story Sound videos with other learning methods and adjust the development of technology and curriculum used in schools.